need to know the steps

y - 3/4 = 5/6

Per additon principle, the same equation can be written as:-

y -3/4 + 3/4 = 5/6 + 3/4 (adding 3/4 on both side of the equation).

-3/4 and +3/4 cancel out each other. So now we are left with just y on right side of the equation.

y = 5/6 + 3/4

Now take common factor of the denominators 4 and 6. The common factor is 12.

Divide 12 by 6 and multiply the result with 5. Then divide 12 by 4 and multiply the result by 3.

y = (10+9)/12

y = 19/12 (final answer)